USE OF INFORMATION TECHNOLOGIES IN FINANCIAL MANAGEMENT - Sanjar Alikulovich Saloxidinov (European Science Publishing, 2024)
The integration of information technologies (IT) in financial management has transformed traditional practices, enhancing efficiency, accuracy, and decision-making capabilities. Modern financial management relies on IT tools for data analysis, reporting, forecasting, and compliance with regulatory standards. This paper explores the role of IT in optimizing financial operations, addressing key challenges, and highlighting its impact on organizational performance. Emphasis is placed on the adoption of cloud-based systems, artificial intelligence, and blockchain technologies, which have redefined the dynamics of financial management in the digital age.
Keywords: Information technologies, financial management, data analysis, decision-making, cloud systems, artificial intelligence, blockchain, organizational performance.